El Dr. Carvallo, Ricardo Palma y los rayos X - Rabinovich, Daniel (2020)
The discovery of X-rays by Wilhelm Conrad Röntgen and their introduction in Peru by Dr. Carvallo is the central theme of the philatelic corner.